STRATEGI MANAJEMEN KEUANGAN BAGI PELAKU USAHA ULTRA MIKRO: OPTIMALKAN KEUNTUNGAN DENGAN HARGA POKOK PRODUKSI - Richatul Jannah; Fitrarena Widhi Rizkyana; Meilani Intan Pratiwi; Risanda Alirastra Budiantoro; Tiara Dwi Lestari; Dina Nur Himmatina; Arif Agus Haidar; Enggarningtyas Retno Pinasti (LP2M Universitas Ibrahimy, 2024)
This community service program was motivated by the limited understanding of ultra-micro business actors (UMi) in Candi Village, Semarang City, regarding financial management and calculating the Cost of Goods Sold (HPP), which affects business sustainability and welfare. The program aimed to provide education on financial management and HPP calculation to help members of the Micro Business Communication Forum (FOKUS) improve their business sustainability and economic welfare. To achieve this, the program employed the Participatory Action Research (PAR) methodology, which involved active participation from the business actors in all stages of the program. The methods used included theoretical education, interactive discussions, and practical HPP calculations relevant to the participants' businesses. The results showed a significant improvement in participants' understanding, enabling them to maintain accurate financial records and separate personal and business finances. The evaluation using the Respondent Achievement Level (TCR) showed scores above 80% in understanding financial management, HPP calculation, and business sustainability, with scores between 60% and 80% in applying this knowledge and improving welfare. The program successfully enhanced the participants' ability to manage their finances, project business profits more effectively, and increase overall business sustainability and welfare.